Eye Tracking Study of Product Packaging - Dhwani Dhanuka, Diptadeep Das, Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Every firm that manufactures any kind of product goes to lengths to enable selling of the said product. Effective communication is very important in getting the right message across and packaging is a kind of communication. Packaging conveys a message that is not so subtle and works on the subconscious of the respondent/customer. For instance, many have agreed on the fact that the packaging of a OnePlus device or an Apple device is very beautiful and gives a very premium feel. Products are packaged differently as per their positioning in the market, and the type of customers they wish to attract. Every customer segment has a different set of needs, wants and aspirations and this, the product needs to be modelled accordingly to fulfil those needs and aspirations. However, along with the product, the packaging also needs to be designed to convey the similar message that the product and the brand wishes to convey. It's a known fact that packaging attracts people in different ways, and packaging is a way of influencing the perceptions of people. How much does it influence really, is possible owing to the various studies available these days. The perceptions related to the packaging of the products is the aim of the study. The methodology that is intended to be used is eye tracking, where the respondents will be shown various products and their packaging from the same product category and asked to rate them based on their perceptions of the product’s pricing, positioning, purity, and premium quotient. Packaging, like advertising, is a medium of conveying message about the product that the company intends to sell, and the analysis of the message and its impact on the consumers is what is of great interest. Eye tracking helped us gauge the attention-grabbing aspects of the product packaging as a result of the heat maps that were achieved from the study. It was easy to understand what caught the attention of the respondents and for how long, to draw inferences about their areas of interests.